German economic and social sciences between the national and the transnational: The Verein für Sozialpolitik, 1872–1952. Issue 2 (February 2017) - McClellan, Steven
Abstract: TheVerein für Sozialpolitik is the preeminent organization of German‐speaking economists in the world. Aside from a brief interruption between during the Nazi period, it has been central in the development of the economic and social sciences in Germany, Austria, and Switzerland but also globally, since 1872. However, historical scholarship on the Verein has been narrowly focused on different thematic or temporal episodes that emphasize conceptual, generational, or political breaks in Germany's turbulent history. This essay gives a brief historical overview of the Verein and the historical literature. It calls for a re‐evaluation that highlights the persistence of the organization as it navigated between national and transnational developments.